Selected Abstracts of the 6th International Congress of UENPS; Valencia (Spain); November 23rd-25th 2016; Session “Gut, gastroenterology and nutrition” - Various Authors, --- (Journal of Pediatric and Neonatal Individualized Medicine (JPNIM), 2016)
Selected Abstracts of the 6th International Congress of UENPS; Valencia (Spain); November 23rd-25th 2016; Session “Gut, gastroenterology and nutrition” ABS 1. MATERNAL FACTORS ASSOCIATED WITH EARLY POSTNATAL WEIGHT LOSS IN EXCLUSIVELY BREASTFED NEONATES • C.J. Lee, T.H. Liu, J.Y. Liou, Y.C. Chen, P.N. Tsao ABS 2. USE OF INSULIN ON PRETERM NEONATES: A GOOD IDEA? • D. Panjwani, G. Holden ABS 3. RISK FACTORS OF DELAYED ONSET OF LACTATION ASSOCIATED NEONATAL TO HYPERBILIRUBINEMIA • C. Kuok, T. Liu, J. Liou, Y. Chen, P. Tsao ABS 4. NUTRITIONAL MANAGEMENT PRACTICE AND POSTNATAL GROWTH OF PRETERM INFANTS • S. Heljic, S. Terzic, H. Maksic, A. Halilovic ABS 5. BREAST MILK EXPRESSION AT THE NICU: EXPERIENCES OF MOTHERS EXPRESSING AT THEIR PRETERM INFANT’S BEDSIDE OR IN A BREAST MILK EXPRESSION ROOM • M. Héon, L. Bell, R. Flacking, C. Catelin ABS 6. RELIABILITY OF THE OM-6050 OSMOMETER STATION TO ANALYSE THE OSMOLARITY OF FORTIFIED BREAST MILK • A. Herranz Barbero, N. Rico Santana, J. Figueras Aloy, F. Botet Mussons, M.D. Salvia Roigés ABS 7. MICROBIOTA OF TERM INFANTS DELIVERED VAGINALLY VS. CESAREAN SECTION – INFLUENCE OF HOME ENVIRONMENT • A. Bartnicka, M. Gałęcka, J. Mazela ABS 8. FACTORS INFLUENCING BREASTFEEDING OF PREMATURE NEWBORNS • N. Skorobogatova, D. Stoniene, J. Ribeliene, E. Meškelevičiūtė, R. Penkauskaitė, R. Tameliene ABS 9. RISK FACTORS REGARDING SUCCESSFUL EXCLUSIVE BREASTFEEDING • M. Miñambres Rodríguez, L.C. Bermúdez Barrezueta, A. Pino Vázquez, M.C. Fernández García-Abril, M. Palomares Cardador, V. Matías ABS 10. THE INFLUENCE OF MOTHER’S ATTITUDE AND MEDICAL STAFF’S ACTIONS ON THE RATES OF BREASTFEEDING OF PRETERM INFANTS • J. Ribeliene, D. Stoniene, N. Skorobogatova, E. Meškelevičiūtė, R. Penkauskaitė, R. Tameliene ABS 11. DONOR HUMAN MILK OFFERS PROTECTION AGAINST LIPID OXIDATIVE STRESS IN PRETERM INFANTS < 32 WEEKS OF GESTATIONAL AGE • J. Kuligowski, A. Parra-Llorca, Á. Sánchez-Illana, M. Aguar, A. Núñez-Ramiro, M. Cernada, M. Gormaz, M. Vento ABS 12. DNA AND PROTEIN OXIDATIVE STRESS IN PRETERM INFANTS LESS THAN 32 WEEKS OF GESTATIONAL AGE FED WITH DONOR HUMAN MILK VERSUS OWN MOTHER’S MILK • A. Parra-Llorca, J. Kuligowski, A. Sánchez-Illana, M. Gormaz, M. Cernada, M. Aguar, A. Núñez-Ramiro, M. Vento ABS 13. RELATIONSHIP BETWEEN ENTERAL NUTRITION GROWTH IN THE EARLY NEONATAL PERIOD AND PHYSICAL AND PSYCHOMOTOR DEVELOPMENT OF VERY PREMATURE INFANTS (VPI) IN THE FIRST 8 CORRECTED MONTHS • A.V. Degtyareva, V. Talvirskaya, D. Amirhanova, M. Narogan ABS 14. THE VERY EARLY DIFFERENCES IN THE BODY COMPOSITION BETWEEN PRETERM NEWBORNS FED WITH FORMULA OR BREAST MILK COMPARED TO THE GROUP OF FULL TERM NEWBORNS • N. Mól, M. Zasada, P. Kwinta ABS 15. ANALYSIS OF THE INFLUENCE OF DIFFERENT TYPES OF DELIVERY AT THE TIME OF FIRST BREASTFEEDING IN HEALTHY TERM NEWBORNS • A.F. Fontes, A. Barroso Pereira ABS 16. HUMAN MILK BANK ESTABLISHMENT IN A NEONATAL UNIT IMPROVES BREASTFEEDING RATES • M. Gormaz, A. Parra-Llorca, M. Cernada, J. Kuligowski, A. Gimeno Navarro, A. Ramón Beltrán, S. Lázaro Beixer, M. Vento, I. Macián ABS 17. LONG-TERM DIFFERENCES IN METABOLIC PATTERN BETWEEN MILK FROM MOTHERS DELIVERING TERM AND PRETERM NEWBORNS: A METABOLOME STUDY • S. Perrone, M. Riccitelli, M. Longini, M.L. Tataranno, S. Negro, M. Tassini, A. Vivi, C. Bracciali, G. Olinda, M. Calderisi, G. Buonocore ABS 18. “NETINCARE” PROJECT: NETWORKING TO IMPROVE HEALTH CARE FOR MOTHERS AND PREMATURE INFANTS IN THE BALTIC REGION AND MOLDOVA • N. Revenco, O. Cirstea, S. Polberger, A. Valiulis, H. Varendi, A. Tiit, K. Abdul, A. Sandgren, K. Young-Keun (DaeHo), G. Husén Strömqvist ABS 19. POSTNATAL GROWTH RATE IN PRETERM INFANTS HOSPITALIZED IN NICU • S. Heljic, S. Terzic, H. Maksic ABS 20. HUMAN MILK BANKING IN GREECE; EXPERIENCE FROM A PUBLIC PERINATAL CENTRE: DATA FROM THE LAST DECADE • I. Ioannou, G. Liosis, G.Vourna, F. Sioubara, K. Dritsakou, A. Tsilia, M. Tzaki ABS 21. MICROVILLUS INCLUSION DISEASE IN A NEWBORN • Ö. Bulut, İ. Mungan Akın, S. Özümüt, D. Büyükkayhan, S. Arslanoğlu, F. Ovalı ABS 22. NECROTIZING ENTEROCOLITIS IN THE FULL-TERM INFANT: ETIOLOGY AND OUTCOME • A. Bouraoui, M. Charfi, M. Ammous, A. Ben Thabet, R. Regaieg, N. Hamida, A. Gargouri ABS 23. REDUCTION OF DONOR HUMAN MILK CONTAMINATION FOLLOWING A NEW COLLECTION PROTOCOL • M. Gormaz Moreno, A. Parra-Llorca, J. Kuligowski, A. Ramón, A. Sánchez-Illana, M. Cernada, S. Lázaro, I. Izquierdo, M. Vento